Requirement of IFT-B–BBSome complex interaction in export of GPR161 from cilia - Nozaki, Shohei (Biol Open, 2019)
The intraflagellar transport (IFT) machinery, which includes the IFT-A and IFT-B complexes, mediates bidirectional trafficking of ciliary proteins. In addition to these complexes, the BBSome, which is composed of eight subunits that are encoded by the causative genes of Bardet-Biedl syndrome (BBS), has been proposed to connect the IFT machinery to ciliary membrane proteins, such as G protein-coupled receptors, to mediate their export from cilia. However, little is known about the connection between the IFT machinery and the BBSome. Using the visible immunoprecipitation assay, we here identified the interaction between IFT38 from the IFT-B complex and BBS1, BBS2 and BBS9 from the BBSome. Furthermore, by analyzing phenotypes of IFT38-knockout cells exogenously expressing wild-type IFT38 or its mutant lacking the ability to interact with BBS1+BBS2+BBS9, we showed that knockout cells expressing the IFT38 mutant have restored ciliogenesis; however, similar to BBS1-knockout cells, they demonstrated significant accumulation of GPR161 within cilia upon stimulation of Hedgehog signaling. These results indicate that the IFT-B–BBSome interaction is required for the export of GPR161 across the ciliary gate.